Examining the link among cross-cultural adaptation, academic satisfaction and word of mouth in the context of international postgraduate students in Malaysia. (2016) - Shafaei, Azadeh; Razak, Nordin Abd
This study was carried out to identify the outcomes of international postgraduate students' adaptation in a public university in Malaysia. A quantitative research approach was employed using online survey to get insights from international postgraduate students enrolled in a Master or PhD level program in a Malaysian public university. Simple random sampling procedure was applied to select the samples of the study. Overall, 206 international postgraduate students responded the questionnaire. The results confirmed the nexus among cross-cultural adaptation, academic satisfaction, and word of mouth in the context of international postgraduate students in Malaysia. Consequently, practical and managerial implications are presented.